Analysis of masticatory cycle efficiency in patients with old and new dentures - Goiato, Marcelo Coelho; Santos, Daniela Micheline dos; Melo Neto, Clovis Lamartine de Moraes (Journal of Orofacial Research, 2019)
Background: The loss of vertical dimension of occlusion, wear of acrylic teeth and the maladaptation of old complete dentures on the tissues can influence chewing of edentulous individuals. The aim of the present study was to analyze the masticatory efficiency in patients with old complete dentures and after 6 months with new complete dentures. Methods: Twenty four edentulous patients between the ages of 65 to 80 years, with old complete dentures (maxillary and mandibular) and without temporomandibular dysfunction were selected. The patients included had decreased vertical dimension of occlusion and deficient dental occlusion. Each patient received artificial food fragments weighing 3 grams and chewed for 35 cycles. The food particles were expelled in granulometric meshes with openings of 2.0, 1.08, 0.42 and 0.20 mm. The analysis occurred with old complete dentures and after 6 months with new complete dentures. Results: Analysis of variance (ANOVA) and Tukey test with 5% significance were performed. After 6 months of wearing new complete dentures, the masticatory efficiency was significantly increased with 0.42 mm mesh, whereas the other meshes did not show increased masticatory efficiency. Conclusion: In general, there was no improvement in the masticatory efficiency of the edentulous individuals after 6 months with new complete dentures.